TRIPUSAT PENDIDIKAN FORMAL SEBAGAI PEMBENTUK KARAKTER PADA PESERTA DIDIK SEKOLAH DASAR - Wiyanto, Agus; Kusumawati, Dian; Masri, Masri; Karimuddin, Karimuddin; Isdarianti, Novi Lidya (Universitas PGRI Semarang, 2025)
Students are the main asset in building the sustainability of the nation and national civilization so that good character values are needed to form students with noble morals. The teachings taught in character education are not limited to the transformation of right and wrong values, but are also related to the cultivation of habits or habituation regarding what is good and what is bad. This research aims to find out how character values are embedded in elementary school students. The qualitative method was carried out through direct observation and in-depth interviews to determine the character values instilled in students through formal education at elementary school level. The results of the research show that there are 18 character values that are embedded in students through habits where in forming individual character it is necessary to have communities of character as character builders which can apparently be found at the elementary school level. Formal education makes students familiar with the rules that embed character values in them so that formal education becomes a shaper in the student's personality that continues.